'Grobkörnige mnemosyne': picturing the First World War in the poetry of Thomas Kling - Duttlinger, C (W. S. Maney & Son Ltd., 2005)
The First World War is a recurrent theme in the work of the contemporary poet Thomas Kling, whose texts engage with this harrowing period of European history through a wide range of personal and official, verbal and visual testimonies. Kling is particularly interested in the role of the Great War as the first modern 'media war' whose depiction in the photography and film has shaped its perception by historical witnesses and present-day viewers alike. However, Kling's primary interest is not in the media as a source of accurate historical evidence; rather, he is interested in the deeply precarious, even paradoxical relationship between the technical media and personal memory. Although film and photography provide tangible testimonies of the past, they also symbolize the irreducible gaps between past and present, between official war propaganda and personal experience. Kling's poems highlight the failure of film and photography to capture an accurate image of the War, its chaos and destruction. The technological limitations of the media, however, have their parallel in the failings of human memory where personal trauma and collective repression likewise prevent any wholly successful engagement with the past.